Rapid Synthesis of Silver Nanoparticles from Fusarium oxysporum by Optimizing Physicocultural Conditions. (10th October 2013) - Birla, Sonal S.; Gaikwad, Swapnil C.; Gade, Aniket K.; Rai, Mahendra K.
Abstract : Synthesis of silver nanoparticles (SNPs) by fungi is emerging as an important branch of nanotechnology due to its ecofriendly, safe, and cost-effective nature. In order to increase the yield of biosynthesized SNPs of desired shape and size, it is necessary to control the cultural and physical parameters during the synthesis. We report optimum synthesis of SNPs on malt extract glucose yeast extract peptone (MGYP) medium at pH 9–11, 40–60°C, and 190.7 Lux and in sun light. The salt concentrations, volume of filtrate and biomass quantity were found to be directly proportional to the yield. The optimized conditions for the stable and rapid synthesis will help in large scale synthesis of monodispersed SNPs. The main aim of the present study was to optimize different media, temperature, pH, light intensity, salt concentration, volume of filtrate, and biomass quantity for the synthesis of SNPs by Fusarium oxysporum .